2022
DOI: 10.1111/sifp.12186
|View full text |Cite
|
Sign up to set email alerts
|

Anemic Women are More at Risk of Injectable Contraceptive Discontinuation due to Side Effects in Ethiopia

Abstract: This paper investigates the importance of women's physiological condition, alongside sociocultural factors, for predicting the risk of discontinuation of the injectable contraceptive due to side effects in Ethiopia. Contraceptive calendar data from the 2016 Ethiopian Demographic and Health Survey were analyzed. Women aged 15–49 who had initiated the injectable contraceptive in the last two years were included in the analysis (n = 1,513). Physiological factors investigated were body mass, iron status, reproduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Early research has suggested that women with poorer nutritional status and harsher workloads may be more at risk of negative bodily experiences (Stevens et al. 2022; Alvergne and Stevens 2021; Vitzthum and Ringheim 2005). Thus, following efforts to personalize health technologies (Harvey et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early research has suggested that women with poorer nutritional status and harsher workloads may be more at risk of negative bodily experiences (Stevens et al. 2022; Alvergne and Stevens 2021; Vitzthum and Ringheim 2005). Thus, following efforts to personalize health technologies (Harvey et al.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, beliefs about the risk of side‐effects experiences are also likely to vary greatly in their seriousness as a concern (Vitzthum and Ringheim 2005; Alvergne and Stevens 2021; Stevens et al. 2022).…”
Section: Language Mattersmentioning
confidence: 99%
See 1 more Smart Citation
“…Most commonly, the data are used to study contraceptive use, such as factors affecting contraceptive discontinuation (e.g., Stevens et al. 2022), method switching (e.g., Ali and Cleland 2010) and contraceptive failure (e.g., Bradley et al. 2019), and to illuminate the dynamics (Maxwell et al.…”
Section: Research With the Calendar Datamentioning
confidence: 99%
“…The few publications based on calendar data demonstrate the material's usefulness. Most commonly, the data are used to study contraceptive use, such as factors affecting contraceptive discontinuation (e.g., Stevens et al 2022), method switching (e.g., Ali and Cleland 2010) and contraceptive failure (e.g., Bradley et al 2019), and to illuminate the dynamics (Maxwell et al 2018) and health consequences (Kannaujiya et al 2020) of birth spacing. Pregnancy termination (e.g., Jain and Winfrey 2017) and patterns of infecundity (e.g., Mascarenhas et al 2012) are also analyzed using calendar data.…”
Section: Research With the Calendar Datamentioning
confidence: 99%